Peningkatan Hasil Belajar IPS Melalui Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Materi Pasar Bagi Peserta Didik Kelas VII B SMP Negeri 2 Ende - Maria Elisabeth Rei Bei (Program Studi Pendidikan Ekonomi, Universitas Flores, 2022)
This study aims to determine the increase in student activity and learning outcomes during cooperative learning with the Number Heads Together type on the market material. Data was collected using observation sheets to determine student activity and end-of-cycle tests to determine learning outcomes. This research is a classroom action research (CAR) conducted in 2 cycles. The results showed that the average value of student learning outcomes in the first cycle was 67.50 and the second cycle was 82.19, an increase of 21.76%. Mastery of student learning in the first cycle of 56.25% and 87.50% in the second cycle increased by 55.56%. Student activity in learning. in the first cycle of 68.69 , classified as quite active, while in the second cycle of 78.34 and classified as active, increased by 14.05 %. From the research data, it can be concluded that the use of the NHT type cooperative learning model can improve learning outcomes in social studies subjects for class VII B students of SMP Negeri 2 Ende in the 2020/2021 academic year.